2017
DOI: 10.1007/s10554-017-1243-7
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial volume computed by 3D rotational angiography best predicts atrial fibrillation recurrence after circumferential pulmonary vein isolation

Abstract: Left atrium (LA) size is a well-studied predictor of atrial fibrillation (AF) recurrence after pulmonary vein isolation (PVI). Yet, there is still little agreement on the best imaging technique to size the LA, and on the most appropriate sizing parameter. Volumetric assessment of LA with three-dimensional rotational angiography (3DRA LA volume index) might be a valid alternative to the commonly used transthoracic echocardiography (TTE LA volume index). The aim of our study was to investigate whether LA volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The results showed that, after applying the navigation technique above, patients with a small LA had successful electrical isolation of the PV. The results of follow-up showed that the proportion of patients maintained sinus rhythm with small LA that remains high, which was consistent with previous studies [1113]. However, these techniques significantly increase X-ray time and dose during mapping and ablation.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that, after applying the navigation technique above, patients with a small LA had successful electrical isolation of the PV. The results of follow-up showed that the proportion of patients maintained sinus rhythm with small LA that remains high, which was consistent with previous studies [1113]. However, these techniques significantly increase X-ray time and dose during mapping and ablation.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of direct comparisons of cardiac parameter values obtained using echocardiography with those obtained by cardiac MRI, numerous earlier studies have found that echocardiography tends to underestimate cardiac volumes as compared to MRI [20][21][22][23][24][25][26][27][28][29][30][31]. However, there are several studies that have shown excellent volume correlations between the two techniques in animal models [32,33] and good correlations for LVEF assessments in human patients [23].…”
Section: Introductionmentioning
confidence: 99%
“…While the technology and application of CB-PVI have undergone significant development over the last years, including advances in balloon design and elimination of the routine use of a bonus freeze, as well as dynamical dosing schemes adapting to the effect of each freeze cycle, no relevant changes have been implemented concerning the periinterventional visualization of the pulmonary vein anatomy. While different pre-(computed tomography [9][10][11], magnetic resonance imaging [12]) and peri-interventional methods (e.g., non-fluoroscopic [13][14][15], rotational angiography [16,17] transesophageal-or intracardiac ultra-sound [10,18]) [4] have been employed or proposed before or during PVI, their use has not been translated into routine CB PVI procedures in the majority of centers that do not utilize the above mentioned techniques. Selective PVA thus has remained the staple of periinterventional PV visualization and is recommended as the de facto gold standard [3,5,19].…”
Section: Discussionmentioning
confidence: 99%